2015
DOI: 10.1155/2015/284360
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Calculation of Radioimmunotherapy with90Y-,177Lu-,131I-,124I-, and188Re-Nanoobjects: Choice of the Best Radionuclide for Solid Tumour Treatment by Using TCP and NTCP Concepts

Abstract: Radioimmunotherapy has shown that the use of monoclonal antibodies combined with a radioisotope like 131I or 90Y still remains ineffective for solid and radioresistant tumour treatment. Previous simulations have revealed that an increase in the number of 90Y labelled to each antibody or nanoobject could be a solution to improve treatment output. It now seems important to assess the treatment output and toxicity when radionuclides such as 90Y, 177Lu, 131I, 124I, and 188Re are used. Tumour control probability (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…One of the current challenges is to maximize the differential response between tumor and healthy tissues. The likelihood for a tumor to be controlled is called the tumor control probability (TCP), while the one for the healthy tissue side-effect is called normal tissue complication probability (NTCP) [11]. These probabilities are represented by a sigmoid function according to the dose, as illustrated in Figure 1.…”
mentioning
confidence: 99%
“…One of the current challenges is to maximize the differential response between tumor and healthy tissues. The likelihood for a tumor to be controlled is called the tumor control probability (TCP), while the one for the healthy tissue side-effect is called normal tissue complication probability (NTCP) [11]. These probabilities are represented by a sigmoid function according to the dose, as illustrated in Figure 1.…”
mentioning
confidence: 99%
“…Firstly, nanoparticles for internal radiotherapy can be labeled with multiple radionuclides, which can make it harder to estimate radiation dosimetry. Recent reports suggest that the combination of different types of beta-emitters could be effective for internal radiotherapy according to the tumor size and uptake of nanoparticles (90,91). Various therapeutic radionuclides with different beta-ray energy such as 90 Y and 177 Lu can be combined for a personalized optimal ratio according to the tumor properties (90).…”
Section: Dosimetry Of Radionanomedicinementioning
confidence: 99%
“…Quantitative measurements of the distribution of an iodine-131 labeled antibody to carcinoembryonic antigen carried out in relation to time by Begent et al [ 9 ] have demonstrated that the maximum tumor uptake of radiolabeled IgG injected into humans occurs within 8 hours after administration. Moreover, Lucas et al [ 10 ] and Xiao et al [ 11 ] demonstrated that rhenium-188 is the best candidate for solid tumors treatment such as for non-small-cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%